Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1139/v85-295
|View full text |Cite
|
Sign up to set email alerts
|

Metal oxide coated p–n junction silicon electrodes for photoelectrochemical solar energy conversion

Abstract: This paper is dedicated lo Professor Camille Srrrzrlor/y 011 rlze occrrsiorr of his 65111 birrhrlayHIROsHl TSUBOMURA, YOSHIHIRO NAKATO, MASAHIRO HIRAMOTO, and HIROYUKI YANO. Can. J. Chem. 63, 1759Chem. 63, (1985. Photoelectrochemical propcrties of p-'-n junction silicon electrodes, abbreviatcd as p+n-Si, coated with thin oxide films of titanium, tungstcn, or iron have been investigated in aqueous solutions of hydrogen iodide and iodine. The films were deposited by electron-beam evaporation of the mctal oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…In this method, two interfaces to separate the processes of the carrier generation at one (photoelectrical junction) and the chemical fuel formation at the other (electrochemical junction) are utilized to replace the single photoelectrochemical interface formed directly by the photoanode with or without a catalyst and the electrolyte. Materials include metals or metallic silicides, 5 wide band gap semiconductors (such as TiO 2 [6][7][8][9] , ZnO, 10 WO 3 , 11 GaN, 12 and Fe 2 O 3 13 ), transparent conducting oxides (TCO, such as mixtures of SnO 2 and In 2 O 3 , 14,15 SnO 2 16,17 and Sb/Ru-SnO 2 18,19 ), transition metal and its oxides polymers (PEDOT:PSS, 27 polyaniline, 28 polyacetylene, 29 and polypyrrole 30 ). Performances of the so-far developed materials or systems greatly depend on the properties of the coating and the two interfaces, such as the barrier height for charge separation, light absorption, photostability/electrochemical stability, hole conductivity, and OER catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, two interfaces to separate the processes of the carrier generation at one (photoelectrical junction) and the chemical fuel formation at the other (electrochemical junction) are utilized to replace the single photoelectrochemical interface formed directly by the photoanode with or without a catalyst and the electrolyte. Materials include metals or metallic silicides, 5 wide band gap semiconductors (such as TiO 2 [6][7][8][9] , ZnO, 10 WO 3 , 11 GaN, 12 and Fe 2 O 3 13 ), transparent conducting oxides (TCO, such as mixtures of SnO 2 and In 2 O 3 , 14,15 SnO 2 16,17 and Sb/Ru-SnO 2 18,19 ), transition metal and its oxides polymers (PEDOT:PSS, 27 polyaniline, 28 polyacetylene, 29 and polypyrrole 30 ). Performances of the so-far developed materials or systems greatly depend on the properties of the coating and the two interfaces, such as the barrier height for charge separation, light absorption, photostability/electrochemical stability, hole conductivity, and OER catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers are now using materials such as TiO 2 to help protect photoabsorbers from oxidation or corrosion in photoelectrochemical reactions. [2][3][4][5][6] In some cases it has been proposed that electrons tunnel through TiO 2 , 2 while in other cases it has been shown that the electrons traverse classically through the conduction band. 4 While both of these methods allow the electron to be transferred through TiO 2 to an electrolyte, the conditions and limitations of each method vary greatly.…”
Section: Introductionmentioning
confidence: 99%
“…Islands of Pt particles were shown to protect n-Si photoanodes in a 4.8 M HBr / 0.03 M Br 2 electrolyte 130. In addition to metals and silicides, conductive oxide coatings such as ITO, SnO 2 , Sb-doped SnO 2 , TiO 2 , Fe 2 O 3 and WO3 have been shown to exhibit stable photoelectrochemical behavior in conjunction with n-Si photoanodes under halide oxidation conditions 76,[131][132][133][134]. Both ion-beam sputtered ITO on n-Si with a RuO 2 co-catalyst, and CVD-grown SnO 2 on n-Si with a Pt co-catalyst, have shown 20 h of stability in either a Cl 2 /Cl -electrolyte (pH = 6.6) or in a I 3 -/I -electrolyte (pH = 1.5), respectively 76.…”
mentioning
confidence: 99%
“…Both ion-beam sputtered ITO on n-Si with a RuO 2 co-catalyst, and CVD-grown SnO 2 on n-Si with a Pt co-catalyst, have shown 20 h of stability in either a Cl 2 /Cl -electrolyte (pH = 6.6) or in a I 3 -/I -electrolyte (pH = 1.5), respectively 76. Yano et al134 reported that thin layers of electron-beam evaporated TiO 2 , Fe 2 O 3 or WO 3 stabilized np + -Si junctions for iodide oxidation, and a TiO 2 -stabilized buried junction np + -Si photoanode exhibited V oc = 580 mV and 330 h of stability for the oxidation of fuming HI.Boron-alloyed Si surfaces also have shown stability for halide oxidation. In one case, an np + -Si junction with a heavily B-enriched surface was formed by drop casting a saturated methanol solution of boron trioxide (BO 3 ) onto Si surfaces, followed by annealing at 1000 °C for 2 h in air 135.…”
mentioning
confidence: 99%